Abitare in equilibri sempre nuovi. La resilienza urbana fra adattamento e trasformazione - Ariani, Camilla (Il sogno della farfalla, 2018)
The recent debate promoted by urbanistic disciplines has been increasingly centred around contemporary towns’ vulnerability and fragility before more frequent natural disasters. At the same time, research on the meaning of urban resilience is spreading. The article outlines the most common interpretations of this term, starting from its first definition in ecology to its usage within social and community domains. As for its first formulations, the author observes how by linking the concept of resilience exclusively to human beings’ relationship with nature, we end up with the proposition of a urbanistic modelling of towns that aims only at maintaining the status quo before external stimuli. The author’s contribution to the study of the term urban resilience aims at highlighting the evolutive potential of interpreting urban resilience as the capability of a continuous transformation of towns as the outcome of a combination of relationships and interactions between people and groups. In order to better comprehend the potential of a propositional interpretation of urban resilience it is adamant to underline the difference between needs and requirements. It is also fundamental to focus on a concept of transformation meant as a continuous change in human beings’ relationships and identities on which towns and communities are based.